The Credibility of Shaykh Nawawi al-Bantani in Ḥadīth Studies: A Study of his Sanad and Ḥadīth Books - Zulfarizal; Kharis, Muhammad Abdul; Ahmad Fudhaili (AL QUDS : Jurnal Studi Alquran dan Hadis, 2025)
Sheikh Nawawi al-Bantani is a great Ulama (Muslim scholar) from the archipelago who managed to go worldwide because of his knowledge. As an Ulama, he dedicated his life to the odyssey of learning and taught it to others. Almost all fields of religious knowledge were mastered by him, including the science of ḥādīth. Although he is well-known as a mufassir, his expertise in the field of ḥādīth is very visible when viewed in detail in his works, especially in the books of Tanqih al-Qawl and Nashaih al-'Ibad. In this study, the writer tries to describe and analyse his credibility in the field of ḥādīth through those two books and his other works. Through qualitative steps accompanied by a historical approach involving documents written by Sheikh Nawawi and other archives, this research has managed to see the special attention given by the Ulama who took part in the Middle East in the field of ḥādīth. The first evidence is the number of ḥādīth narrations that he included in the books he wrote. Second, he studied a lot of dirāyah ḥādīth books, as can be seen in the book al-'Iqd al-Farīd min Jawāhir al-Asānīd by Sheikh Yāsīn al-Fādānī. Third, he had books containing the narration of ḥādīth, namely Tanqih al-Qawl and Nashaih al-'Ibad.